GA3 and Other Signal Regulators (MeJA and IAA) Improve Xanthumin Biosynthesis in Different Manners in Xanthium strumarium L. - Changfu Li; Fangfang Chen; Yansheng Zhang (Molecules, 2014)
Xanthanolides from Xanthium strumarium L. exhibit various pharmacological activities and these compounds are mainly produced in the glandular trichomes of aerial plant parts. The regulation of xanthanolide biosynthesis has never been reported in the literature. In this study, the effects of phytohormonal stimulation on xanthumin (a xanthanolide compound) biosynthesis, glandular trichomes and germacrene A synthase (GAS) gene expression in X. strumarium L. young leaves were investigated. The exogenous applications of methyl jasmonate (MeJA), indole-3-acetic acid (IAA), and gibberrellin A3 (GA3) at appropriate concentrations were all found to improve xanthumin biosynthesis, but in different ways. It was suggested that a higher gland density stimulated by MeJA (400 µM) or IAA (200 µM) treatment caused at least in part an improvement in xanthumin production, whereas GA3 (10 µM) led to an improvement by up-regulating xanthumin biosynthetic genes within gland cells, not by forming more glandular trichomes. Compared to the plants before the flowering stage, plants that had initiated flowering showed enhanced xanthumin biosynthesis, but no higher gland density, an effect was similar to that caused by exogenous GA3 treatment.